2014
DOI: 10.1136/sextrans-2014-051535
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection withChlamydia trachomatis, Neisseria gonorrhoeae and Trichomonas vaginalis: a cross-sectional analysis of positivity and risk factors in remote Australian Aboriginal communities

Abstract: Australian and New Zealand Clinical Trials Registry ACTRN12610000358044.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 29 publications
(35 reference statements)
4
37
0
1
Order By: Relevance
“…We did not stratify our modelled population by levels of sexual activity, on the basis that, as noted above, it has been observed in subpopulations where TV infection is common, that prevalence tends to be similar across all age groups in the sexually active population despite higher partner acquisition rates in younger age groups 13. However, due to a lack of data, it is difficult to ascertain if this observation holds for populations where TV infection is rare.…”
Section: Discussionmentioning
confidence: 99%
“…We did not stratify our modelled population by levels of sexual activity, on the basis that, as noted above, it has been observed in subpopulations where TV infection is common, that prevalence tends to be similar across all age groups in the sexually active population despite higher partner acquisition rates in younger age groups 13. However, due to a lack of data, it is difficult to ascertain if this observation holds for populations where TV infection is rare.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent clinic-based studies have been undertaken to determine testing rates, prevalence, and incidence of STIs, particularly in remote settings, and confirmed the highly elevated rates of STIs in comparison to nonindigenous young Australians. 8,9 These studies have further shown testing rates to be higher in Aboriginal women than men, probably related to more regular health service attendance providing more opportunities for testing in women. 10 There remains a gap in that no community-based data collection has ever been reported on STI testing and diagnoses in a sample of young Aboriginal people.…”
Section: Introductionmentioning
confidence: 96%
“…A study conducted in 67 remote Aboriginal communities in Australia in 2009–2011 found that the prevalence of chlamydia and gonorrhoea among people aged 16–24 years was 21% and 18% respectively . In the same communities, among people aged 16–19 years, 33% of male and 49% of female health care centre attendees were diagnosed with either chlamydia, gonorrhoea or trichomonas in the previous year . It is difficult to provide a clear comparison between these rates and other regions in Australia; however, the prevalence of chlamydia for young people attending general practice or other community settings was 4% among males aged less than 30 years and 5% in females aged less than 25 years …”
Section: Sexually Transmissible Infections In Remote Aboriginal Commumentioning
confidence: 99%